Announcements (The Review of Asset Pricing Studies, 2013)
Journal Article Announcements Get access The Review of Asset Pricing Studies, Volume 3, Issue 2, December 2013, Page 179, https://doi.org/10.1093/rapstu/rat001 Published: 11 November 2013